Active Learning Management for Foreign Teachers toward Thai Students’ English Language Learning - ลอมศรี สกานต์; พัฒนพงศา นรินทร์ชัย (Community and Social Development Journal, 2016)
This research aims to study the Active Learning quality of foreign English teachers. A handbook for teaching English in an Active Learning was developed as guidelines and to compare the results of Active Learning towards learning English for Grade 9 students in Chiang Mai and Lamphun. The populations in this research were 23 Private schools (Except the Foundation School) Grade 9 in Chiang Mai and 3 schools from Lamphun. After surveyed, there were 5 schools that willing to participate. Then classified the samples into two groups, 3 schools for experimental group and 2 schools for control group. A quasi-experimental design was used. Data was collected using a questionnaire, surveys, score points collected between semester, final scores, and the pre-test and post-test scores. The results showed that 1) The use of Active Learning for experimental school teachers increased. 2) An Active Learning Handbook for foreign teachers was appropriate. 3) The result of the experimental and control students’ English score, significant at 0.05, were as follow: (1) Before the experiment, the experiment and control students’ English score were not different. (2) For the experimental group, the English score after the experiment was higher than before the experiment. (3) The different score (post-pre) of the experimental group was higher than the control group.